Encyclopedia & dictionary of medicine, nursing, & allied health (Saunders, 2003)
Encyclopedia and dictionary serves as a current, comprehensive vocabulary source for the health sciences. Includes 3,900 new entries, with archaic and obsolete terms deleted. The latest changes for diagnosis-related groups, nursing diagnoses, and other key nursing taxonomies are included. Revised tables and illustrations.